2007
DOI: 10.1111/j.1365-2672.2007.03319.x
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic community analysis with CARD-FISH in comparison with FISH in ultra-oligotrophic ground- and drinking water

Abstract: Aims:  We compared the applicability of catalysed reporter deposition fluorescence in situ hybridization (CARD‐FISH) and FISH to enumerate prokaryotic populations in ultra‐oligotrophic alpine groundwaters and bottled mineral water Methods and Results:  Fluorescent oligonucleotide probes EUB338 and EUB338mix (EUB338/EUB338‐II/EUB338‐III) were used to enumerate bacteria and probes EURY806 and CREN537 for Euryarchaea and Crenarchaea, respectively. Improved detection of Planctomycetales by probe EUB338‐II was test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
3
25
0
2
Order By: Relevance
“…The newly developed protocol is based on the CARD-FISH protocol described by Wilhartitz et al (37), with modifications. Samples were fixed with 4% PFA and filtered on CB04 filters (black; Ø, 25 mm; pore size, 0.4 m; AES Chemunex).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly developed protocol is based on the CARD-FISH protocol described by Wilhartitz et al (37), with modifications. Samples were fixed with 4% PFA and filtered on CB04 filters (black; Ø, 25 mm; pore size, 0.4 m; AES Chemunex).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, previous studies (24,34) have shown that the fluorescence signals of standard FISH-labeled microorganisms were too weak to be detected with solid-phase cytometry. Catalyzed reporter deposition-FISH (CARD-FISH) is one methodical improvement to increase the signal intensity of microorganisms (30,33,37). The rRNAtargeted oligonucleotide probe is labeled with horseradish peroxidase (HRP).…”
mentioning
confidence: 99%
“…The non-EUB-338 probe (4) was also included as an additional control to monitor nonspecific probe binding. For V. souniana, cell wall permeabilization was required (by incubation with proteinase K 4U/ml at 37°C for 1 h; Sigma, St. Louis, MO) due to its protein-rich cell wall (70,74).…”
Section: Methodsmentioning
confidence: 99%
“…1995 ;Pernthaler et al . 2002 ;Wilhartitz et al ., 2007 ;Eickhorst and Tippkötter, 2008 ;Shiraishi et al ., 2008 ;Schramm and Amann 2008 RISA/ribosomal intergenic spacer Fast and large numbers of samples possible. Automatic approach possible.…”
Section: Referencementioning
confidence: 95%